2016
DOI: 10.1093/imrn/rnw174
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of Odd Degree Characters and Natural Correspondences

Abstract: Abstract. Let q be an odd prime power, n > 1, and let P denote a maximal parabolic subgroup of GLn(q) with Levi subgroup GLn−1(q) × GL1(q). We restrict the odd-degree irreducible characters of GLn(q) to P to discover a natural correspondence of characters, both for GLn(q) and SLn(q). A similar result is established for certain finite groups with self-normalizing Sylow p-subgroups. We also construct a canonical bijection between the odd-degree irreducible characters of Sn and those of M , where M is any maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 28 publications
0
62
0
Order By: Relevance
“…In [4] it is shown that the process described above defines a bijection α n between Irr 2 (S n ) and H := H(2 n1 ) × · · · × H(2 nt ). The description of the Sylow 2-subgroup structure of S n given in Section 2.3, together with Theorem 1.1 implies the existence of a bijection β n between H and Irr 2 (P n ).…”
Section: Canonical Bijectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [4] it is shown that the process described above defines a bijection α n between Irr 2 (S n ) and H := H(2 n1 ) × · · · × H(2 nt ). The description of the Sylow 2-subgroup structure of S n given in Section 2.3, together with Theorem 1.1 implies the existence of a bijection β n between H and Irr 2 (P n ).…”
Section: Canonical Bijectionsmentioning
confidence: 99%
“…Let n = 6 and let P 6 be a Sylow 2-subgroup of S 6 . Then (4), and K 6 = {(6), (5, 1), (4, 2), (3 2 ), (2 3 ), (2 2 , 1 2 ), (2, 1 4 ), (1 6 )} ⊆ P (6).…”
Section: Canonical Bijectionsmentioning
confidence: 99%
See 3 more Smart Citations